Glacier-dammed lake outburst events of Gornersee, Switzerland - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Werder, Mauro; id_orcid:0 000-0003-0137-9377; Funk, Martin; Hock, Regine (Journal of Glaciology, 2007)
ISSN:0022-1430 ISSN:1727-5652